1994
DOI: 10.1002/gps.930090711
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of real versus simulated electroconvulsive therapy in depressed elderly patients

Abstract: SUMMARYThe results of the Nottingham electroconvulsive therapy (ECT) trial were examined to compare the response of patients aged 60 and over to real versus simulated ECT. The outcome of patients given real compared to simulated ECT was significantly better immediately after six study treatments. Unilateral ECT was an effective as bilateral treatment. The small number of patients studied did not allow for definitive conclusions on whether patients responded sooner to bilateral relative to unilateral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Review of effectiveness: From two reviews, 15 , 16 four RCTs were located. The only study that compared ECT with placebo (sham ECT) in older people 17 showed that ECT was effective. ECT has been widely used to treat severe depression in older people, and retrospective studies have concluded that it is reasonably safe to use, even in patients aged over 80 years 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Review of effectiveness: From two reviews, 15 , 16 four RCTs were located. The only study that compared ECT with placebo (sham ECT) in older people 17 showed that ECT was effective. ECT has been widely used to treat severe depression in older people, and retrospective studies have concluded that it is reasonably safe to use, even in patients aged over 80 years 14 .…”
Section: Resultsmentioning
confidence: 99%
“…ECT is a highly effective treatment for late‐life depression, 147 and may have a more rapid therapeutic effect than drug therapy 148 . However, because of the need for general anesthesia and adverse events such as amnesia, ECT is used only when patients have severe suicidal ideation, undernutrition, or difficulties with antidepressant treatment.…”
Section: Section C Treatmentmentioning
confidence: 99%
“…ECT has an important role in depression with suicidality and psychosis. [64][65][66] Vagal nerve stimulation and transcranial magnetic stimulation are two other therapies for pharmacotherapy-resistant depression, FDA-approved in 2005 and 2008, respectively. 59…”
Section: Treatment-resistant Lld: Pharmacological Strategiesmentioning
confidence: 99%